Construct validity of the physical activity neighborhood environment scale-Oman - De Siqueira, Gustavo; Mabry, Ruth; Al Siyabi, Huda; Adeel, Ahmad; Malaj, Sadmira; Oyeyemi, Adewale (Frontiers in Public Health, 2023)
This study aims to examine the construct validity of Physical Activity Neighborhoods Environment Scales, Oman (PANES-O) and compare the subjective perceptions with objective measures in Muscat, Oman. Walkability index scores were calculated for 35 study areas in Muscat and five low and 5 high walkable areas were randomly selected subsequently. A community survey was then conducted in November 2020 in each study area using the 16-item PANES-O instrument to measure the participants’ perception of net residential density, land use mix, infrastructure, safety, aesthetics and street connectivity. Due to pandemic restrictions, a social media-based purposive sampling strategy was utilized to complete digital data collection. Significant differences in perceptions across 12 of the 16-item PANES tool confirmed that 6 of the 7 subscales were significantly sensitive to built environment attributes between the low and high walkable study areas. Respondents in high walkable neighborhoods perceived their areas as having greater access to destinations, and easy access to public transport. more places to be active, better infrastructure, and better aesthetic qualities. PANES-O also was able to rate high walkable neighborhoods to be higher in residential density and land-use mix compared to the low walkable neighborhoods. These results provide strong support for the construct validity of PANES-O, confirming that it is a promising tool for assessing environmental perceptions related to physical activity in Oman. PANES-O could be used to generate the needed evidence on the most cost-effective and socio-culturally appropriate approaches to improving the built environment to promote physical activity.